Spectroscopy of Freons: Submillimeter-Wave Rotational Spectrum of C35Cl3F Molecule (Freon-11) in the Ground Vibrational State - Gerasimov, V. G.; Dyubko, S. F.; Efremov, V. A.; Efimenko, M. N.; Katrich, A. A. (Видавничий дім «Академперіодика», 2013)
Спектроскопия фреонов: субмиллиметровый вращательный спектр молекул C35Cl3F (фреон-11) в основном колебательном состоянии